THE ROLE OF ECONOMIC POLICY UNCERTAINTY AND ENVIRONMENTAL POLICIES IN SHAPING ENVIRONMENTAL SUSTAINABILITY: EVIDENCE FROM BRICS NATIONS : Received: 3rd April 2025, Revised: 12th May 2025, Accepted: 20st May 2025, Date of Publication: 12th November 2025 - Eugene Ray Atsi, (PEOPLE: International Journal of Social Sciences, 2025)
The intensity of environmental pollution has contributed to an immense depletion in our ozone layer and a recession in the global economy. Factors such as uncertainties in economic policies have resulted in the changes in fiscal and monetary policies, serving as limitation for environmental sustainability. However, this study seeks to explore how economic policy uncertainty (EPU) can interact with environmental policies (EPI) to enhance environmental sustainability in BRICS countries. It employs the clustered pooled least square (PLS) and Fixed-effect (FE) models to analyze data from 2000-2022. The findings indicate that EPU increases carbon dioxide (CO2) emissions whiles EPI reduces CO2 emissions. However, integrating EPU and EPI mitigates CO2 emissions in BRICS nations. The study therefore asserts that policymakers can stabilize environmental commitment by implementing long-term, legally binding frameworks, ensuring that environmental policies remain consistent and unaffected by political or economic uncertainties.